Role of Inhaled Corticosteroids in Pediatric Asthma and Virus induced wheeze - Rajinder Singh (Pediatric Review: International Journal of Pediatric Research, 2025)
Inhaled corticosteroids (ICS) are one of the important components of childhood asthma pharmacotherapy and a common first-line treatment. Treatment with ICS decreases asthma mortality and morbidity reduces symptoms, improves lung function, improves symptoms in childhood viral-induced wheezing and reduces the number of asthma exacerbations. This study reviews the role of ICS in childhood asthma, including their mechanism of action, clinical efficacy, safety profile, and adherence challenges. The benefits of ICS in controlling symptoms and reducing morbidity outweigh their potential risks when used appropriately in proper dosages. Strategies for optimizing ICS therapy and addressing concerns about long-term use are also discussed.